1998
DOI: 10.1002/(sici)1097-0223(199804)18:4<339::aid-pd265>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Fetal intrahepatic hyperechogenic foci: prenatal ultrasound diagnosis and outcome

Abstract: Fetal intrahepatic hyperechogenic foci were found in 7 out of 7260 patients (1:1037) referred to our prenatal centre for a fetal anomaly scan because of an increased risk or suspected presence of fetal structural anomalies. The gestational age varied between 20 and 32 weeks (mean 24 weeks). Fetal karyotyping in 3 out of 7 fetuses resulted in one case of trisomy 18. Additional anomalies were diagnosed in both this case and a case of combined hyperechogenic liver foci, encephalocoele, and unilateral renal agenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have mainly focused on liver calcifications, which have been reported in 2.2% to 4.2% of cases in autopsy studies [ 2 , 3 ], and with an estimated incidence ranging from 1:260 to 1:1750 in ultrasound screening [ 4 6 ]. When identified by ultrasound, cases with calcification as the only aberrant finding usually have a good outcome, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have mainly focused on liver calcifications, which have been reported in 2.2% to 4.2% of cases in autopsy studies [ 2 , 3 ], and with an estimated incidence ranging from 1:260 to 1:1750 in ultrasound screening [ 4 6 ]. When identified by ultrasound, cases with calcification as the only aberrant finding usually have a good outcome, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, when identified together with other abnormalities, the prognosis is poor. Studies have suggested association of calcifications with infection [ 9 , 11 , 12 ], circulatory compromise [ 2 , 13 ], and chromosomal abnormalities [ 2 , 4 6 , 8 , 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This case demonstrates how full antenatal and postnatal investigations have been essential to clarify the apparently incidental association between Down syndrome, liver hyperechogenicity and abnormal plasma levels of liver enzymes. The rate of abnormal karyotypes is indeed extremely low in fetuses with this ultrasonic feature, unless structural anomalies are found (Bronshtein and Blazer, 1995;Koopman and Wladimiroff, 1998), and there is no reasonable explanation, but another unrelated disease, for the abnormal liver tests. On the other hand, a variety of causes leading to calcification and/or Daffos F andForrestier F, 1988.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of isolated fetal liver calcifications is undetermined while the incidence of whole fetal liver calcifications was estimated as 5.7-10/10000 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . It may be due to the fact that our hospital is a referral center so we were found the incidence higher than other publications.…”
Section: Dicussionmentioning
confidence: 99%
“…Parenchymal calcifications were detected especially at pregnancies which complicated with intrauterine infections, primary or methastatic liver tumours, gall-bladder stones and vasculare thrombosis (2,6,7,13) . Chromosomale anomalies also might cause fetal liver calcifications (2,8) . calcifications but it has been reported in the literature that the probability of chromosomal anomalies in patients without concomitant abnormalities is very low.…”
Section: Dicussionmentioning
confidence: 99%